The Development of a Conceptual Framework for Hybridity and Sustainability in Social (Micro-) Franchises - Ntloko, Welekazi S’thandwa (Stellenbosch : Stellenbosch University, 2026)
Thesis (PhD)--Stellenbosch University, 2026.